Enabling apple DOS to create & process index files - Ang, Manchan (Animo Repository, 1986)
In the Philippines, the Apple microcomputer is widely implemented for business. Applications for business need index files. The Apple Disk Operating System (DOS) does not have index files and provides only the sequential and random files. Thus, Apple users make use of an additional software layer that can provide index files. However, in doing so, they encounter setbacks in Apple such as limited memory and occasional malfunctioning. This study solves this problem by enabling Apple DOS to create and process index files. This is done by adding 9 commands to the DOS set of commands that can perform the basic index file operations. These additional commands make up the Index File Software. To ensure the high performance of the Index File Software, its design is given much emphasis. Efficient and accepted design and process concepts are obtained from IBM VSAM key-sequenced file and implemented in the Index File Software. The benchmark provided will illustrate the software's high performance.